A Decentralized Signcryption Scheme Based on CFL - Leyi Shi; Mengting Liu (Sensors)
The rapid advancement of quantum computing technology poses a significant threat to conventional public key cryptographic infrastructure. The SM2 (state key cryptography algorithm no. 2) elliptic curve public key cryptographic algorithm, which adopts elliptic curve cryptography, has demonstrated strong resistance to quantum attacks. However, existing signcryption schemes remain vulnerable due to their reliance on a single certification authority (CA) managing all keys. The cryptography fundamental logics (CFL) authentication process eliminates the need for third-party involvement, achieving decentralized authentication and reducing the burden on certificate generation centers. Therefore, a decentralized signcryption scheme based on CFL was proposed using the SM2 national cryptographic algorithm. Unlike traditional signcryption schemes, this approach does not depend on the certification authority’s private key during the public–private key generation process. This innovation helps avoid risks associated with certification authority private key leakage and ensures decentralized characteristics. The proposed scheme was rigorously verified under the random oracle model (ROM) and based on the complexity assumption of the elliptic curve Diffie–Hellman (ECDH) problem. The theoretical analysis and experimental results demonstrate that compared to traditional methods, the proposed scheme exhibits higher efficiency in communication and computation. Specifically, the proposed scheme reduces computational overheads by approximately 30% and communication overheads by approximately 20% in practical working environments. These quantitative improvements highlight the scheme’s promising application prospects and practical value.